Assessment of the negative effects of military operations on the territory of Vyshgorod district of Kyiv region - Butenko, Ye.; Kuznetsova, O.; Petrychenko, S. (Land Management, Cadastre and Land Monitoring, 2024)
The article identifies the negative factors that have arisen as a result of military operations on the territory of Ukraine. The article presents the values of environmental damage in terms of quantitative indicators of the impact of military operations on the natural environment and the country’s economy based on open data of the State Environmental Inspectorate of Ukraine. The destruction, which includes the loss of biodiversity, production facilities, air pollution, land, open water bodies, forests and the entire ecosystem, is considered. The article analyses the impact of negative factors that arose after the full-scale invasion on 24.02.2022 and affected land use (using the example of Kyiv region). The area of land plots by land category that was under occupation from 24 February 2022 to 02 April 2022 was calculated. Based on the proposed method of analysis, it will be possible to calculate the area of land, taking into account its designated purpose, ownership and type of use. The number of territorial communities affected by the negative consequences of hostilities is given. The assessment of the negative effects of hostilities is carried out in the long term, as it requires the collection and analysis of a large amount of data. However, this is an extremely important process for determining the necessary resources and strategies for restoring the territory and infrastructure. In the future, the data on monitoring the state of the environment from the negative impact of hostilities will become the basis for making informed decisions on the restoration and development of territories, ensuring a balanced approach to the conservation of natural resources and economic recovery of the affected regions of our country. Keywords: assessment of the negative consequences of military operations, impact assessment, economic development of the territory, territorial communities, land and soil protection, monitoring, land management.